An investigation on manufacturing of the straight bevel gear using end mill by CNC milling machine - Özel, C; Inan, A; Özler, L (Asme-Amer Soc Mechanical Eng, 2005)
Accurate manufacturing of bevel gears is an important problem for small workshops because the module milling cutters used for manufacturing are not accurate enough for the task. In this study, manufacturing of straight bevel gears is investigated by using end mills in CNC milling with a vertical machining center. By using this method, use of auxiliary apparatus, special cutters (such as the circular cutter the rack cutter, etc.), and special machine tools are not required. For the study, first the straight bevel gear was modeled by Tredgold's approach and manufacturing equations of the straight bevel gear were obtained. For the straight bevel gear manufacturing, a macro program was prepared and used. Afterward, the straight bevel gear was manufactured ky using this program in a CNC milling inachine, the Dyna 2900 machine. The results of the measurement data for single tooth on the gear manufactured and the theoretical values are presented and discussed.
Keywords: straight bevel gear; end mill; CNC milling machine; macro program